C03 Modifiers of instability and age at onset in HD: haplotype study in the Portuguese population. (16th November 2010) - Ramos, E M; Gillis, T; Mysore, J; Abuelneel, K; Gusella, J; MacDonald, M; Lee, J-M; Alonso, I; Sequeiros, J
Abstract : Background: Huntington's disease (HD) is a progressive neurodegenerative disorder characterised by motor, cognitive and psychiatric symptoms. The causal mutation is the expansion of a polymorphic CAG tract (>35 CAG repeats) in the HD gene. Previous haplotype studies of Portuguese HD families concluded that the current HD chromosomes may have originated from several different ancestral chromosomes four. Aims: To assess the role of HD cis elements as modifiers of repeat instability and age at onset. Methods/techniques: We have now performed an extensive haplotype study of both normal and HD chromosomes for the ∼1.17 Mb 4p16.3 region flanking the HD gene in 127 Portuguese families. Results/outcome: Our results revealed a variety of haplotypes and: (1) an enrichment of certain haplotypes (A and C) on the HD chromosomes, (2) smaller genetic diversity as the CAG repeat size increases, with large normal allele range chromosomes sharing the same major haplotypes as the HD chromosomes, three association of haplogroup C with CAG instability in intergenerational transmissions on HD chromosomes while haplogroup D seemed to be more stable. Moreover, preliminary analysis suggested that haplogroup C may be a risk factor for earlier disease onset whereas haplotypes A and B may be relatively protective although the data set is relatively small. Conclusions: Our preliminary results identified particular haplotypes associated with specific HD features, particularly CAG instability. These findings may be relevant for genetic counselling, where, given the general relationship of CAG size to age at onset, understanding of CAG instability can be an important issue.